A 3d geological model of the 1963 vajont landslide - Bistacchi, Andrea; Massironi, Matteo; Superchi, Laura; Zorzi, Luca; Francesca, Roberto; Giorgi, Massimo; Chistolini, Filippo; Genevois, Rinaldo (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value=""1":2,"2":"The Vajont landslide has been the object of several studies because of its catastrophic consequences and particular evolution. Several qualitative or quantitative models have been presented in the last 50 years, but a complete explanation of all relevant geological and mechanical processes still remains elusive. In order to better understand the mechanics and dynamics of the 1963 event, we have reconstructed the first 3D geological model of the landslide, which allowed us to accurately investigate the landslide structure and kinematics. The input data for the model consisted in: pre- and post-landslide geological maps, pre- and post-landslide orthophotos, pre- and post-landslide digital elevation models, structural data, boreholes, and geophysical data. All these data have been integrated in a 3D geological model implemented in Gocad, using the implicit surface modelling method. Results of the 3D geological model include the depth and geometry of the sliding surface, the volume of the two lobes of the landslide accumulation, kinematics of the landslide in terms of the vector field of finite displacement, and high quality meshes useful for mechanical simulations. The latter can include information about the stratigraphy and internal structure of the rock masses and allow tracing the displacement of different material points in the landslide from the pre-1963-failure to the post-landslide state. As a general geological conclusion, we may say that the structural analysis and the 3D model allowed us to recognize very effectively a sliding surface, whose non-planar geometry is affected by the interference pattern of two regional-scale fold systems. The landslide is partitioned into two distinct and internally continuous rock masses with a distinct kinematics, which are characterised by a very limited internal deformation during the slide. The continuity of these two large blocks points to a very localized deformation, occurring along a thin, continuous and weak cataclastic horizon."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">The Vajont landslide has been the object of several studies because of its catastrophic consequences and particular evolution. Several qualitative or quantitative models have been presented in the last 50 years, but a complete explanation of all relevant geological and mechanical processes still remains elusive. In order to better understand the mechanics and dynamics of the 1963 event, we have reconstructed the first 3D geological model of the landslide, which allowed us to accurately investigate the landslide structure and kinematics. The input data for the model consisted in: pre- and post-landslide geological maps, pre- and post-landslide orthophotos, pre- and post-landslide digital elevation models, structural data, boreholes, and geophysical data. All these data have been integrated in a 3D geological model implemented in Gocad, using the implicit surface modelling method. Results of the 3D geological model include the depth and geometry of the sliding surface, the volume of the two lobes of the landslide accumulation, kinematics of the landslide in terms of the vector field of finite displacement, and high quality meshes useful for mechanical simulations. The latter can include information about the stratigraphy and internal structure of the rock masses and allow tracing the displacement of different material points in the landslide from the pre-1963-failure to the post-landslide state. As a general geological conclusion, we may say that the structural analysis and the 3D model allowed us to recognize very effectively a sliding surface, whose non-planar geometry is affected by the interference pattern of two regional-scale fold systems. The landslide is partitioned into two distinct and internally continuous rock masses with a distinct kinematics, which are characterised by a very limited internal deformation during the slide. The continuity of these two large blocks points to a very localized deformation, occurring along a thin, continuous and weak cataclastic horizon.